2022
DOI: 10.1038/s41598-022-22126-y
|View full text |Cite
|
Sign up to set email alerts
|

Regional lymph node metastasis detected on preoperative CT and/or FDG-PET may predict early recurrence of pancreatic adenocarcinoma after curative resection

Abstract: The objective of this study was to evaluate the role of regional lymph node (LN) metastasis detected on preoperative CT and/or 18F-fluoro-2-deoxyglucose-positron emission tomography (FDG-PET) scans in the prediction of early tumor recurrence after curative surgical resection of pancreatic ductal adenocarcinoma (PDAC). This retrospective study included 137 patients who underwent upfront surgery with R0 resection of PDAC between 2013 and 2016. Regional LN metastasis was identified using two criteria: positive fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The PET examination relies on the metabolic characteristic of tissues, and it is proposed to be able to precisely diagnose LN metastasis. However, the sensitivity of PET is reported as unsatisfactory previously as well 24 . Also, considering the radioactivity and high price, the PET examination was actually not commonly used in clinical.…”
Section: Discussionmentioning
confidence: 95%
“…The PET examination relies on the metabolic characteristic of tissues, and it is proposed to be able to precisely diagnose LN metastasis. However, the sensitivity of PET is reported as unsatisfactory previously as well 24 . Also, considering the radioactivity and high price, the PET examination was actually not commonly used in clinical.…”
Section: Discussionmentioning
confidence: 95%
“…To address the low sensitivity of both modalities, we combined the findings of 18 F-FDG PET/CT and CT to identify suspicious regional LNs, resulting in a modest improvement in sensitivity (32.0%) and a slight reduction in specificity (84.8%). Despite the low sensitivity of both modalities, the prognostic value of suspicious regional LNs detected using 18 F-FDG PET/CT or CT was also recently reported [ 38 ]. Taken together, the presence of suspicious regional LN detected using 18 F-FDG PET/CT or CT suggests the presence of pathological LN metastasis and a high risk of recurrence in patients with resectable PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…PDAC with artery involvement has been reported in association with advanced tumor characteristics, lower R0 resection rate, and higher recurrence rate [27][28][29]. With respect to the cN stage, a number of studies [14,21,30] reported that the detection of lymph node metastasis preoperative CT scans (cN1/2) was a useful predicter of ER. The nomogram integrating the deep learning model outputs and these two radiological variables showed an improved predictive performance over the clinical model.…”
Section: Discussionmentioning
confidence: 99%